Boosted coupling of ATP hydrolysis to substrate transport upon cooperative estradiol‐17‐β‐D‐glucuronide binding in a Drosophila ATP binding cassette type‐C transporter. Issue 2 (4th January 2018) - Karasik, Agnes; Victoria Ledwitch, Kaitlyn; Aranyi, Tamas; Varadi, András; Roberts, Arthur; Szeri, Flora
Abstract : ATP binding cassette type‐C (ABCC) transporters move molecules across cell membranes upon hydrolysis of ATP; however, their coupling of ATP hydrolysis to substrate transport remains elusive. Drosophila multidrug resistance‐associated protein (DMRP) is the functional ortholog of human long ABCC transporters, with similar substrate and inhibitor specificity, but higher activity. Exploiting its high activity, we kinetically dissected the catalytic mechanism of DMRP by using E2 ‐D‐glucuronide (E2 G), the physiologic substrate of human ABCC. We examined the DMRP‐mediated interdependence of ATP and E2 G in biochemical assays. We observed E2 G‐dependent ATPase activity to be biphasic at subsaturating ATP concentrations, which implies at least 2 E2 G binding sites on DMRP. Furthermore, transport measurements indicated strong nonreciprocal cooperativity between ATP and E2 G. In addition to confirming these findings, our kinetic modeling with the Complex Pathway Simulator indicated a 10‐fold decrease in the E2 G‐mediated activation of ATP hydrolysis upon saturation of the second E2 G binding site. Surprisingly, the binding of the second E2 G allowed for substrate transport with a constant rate, which tightly coupled ATP hydrolysis to transport. In summary, we show that the second E2 G binding—similar to human ABCC2—allosterically stimulates transport activity of DMRP. Our data suggest that this is achieved by a significant increase in the coupling of ATP hydrolysis to transport.—Karasik, A., Ledwitch, K. V., Arányi, T., Varadi, A., Roberts, A., Szeri, F. Boosted coupling of ATP hydrolysis to substrate transport upon cooperative estradiol‐17‐β‐D‐glucuronide binding in a Drosophila ATP binding cassette type‐C transporter. FASEB J. 32, 669‐680 (2018). www.fasebj.org